2020
DOI: 10.1038/s41598-020-60329-3
|View full text |Cite
|
Sign up to set email alerts
|

Neuroestrogen synthesis modifies neural representations of learned song without altering vocal imitation in developing songbirds

Abstract: Birdsong learning, like human speech, depends on the early memorization of auditory models, yet how initial auditory experiences are formed and consolidated is unclear. In songbirds, a putative cortical locus is the caudomedial nidopallium (NCM), and one mechanism to facilitate auditory consolidation is 17β-estradiol (E2), which is associated with human speech-language development, and is abundant in both NCM and human temporal cortex. Circulating and NCM E2 levels are dynamic during learning, suggesting E2's … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 149 publications
(208 reference statements)
1
4
0
Order By: Relevance
“…Interestingly, the percentage of aromatase neurons detected by both the rabbit (Ikeda et al, 2017) and the sheep antibodies (present study) was slightly higher in the ventral NCM compared to the dorsal NCM (90.5% in vNCM, 86.5% in dNCM) which could partially account for this region-dependence. The dorsal NCM is also known to contain more cells as shown by DAPI staining (Vahaba et al, 2020) and confirmed in the present study that could explain the lower proportion of aromatase positive cells while the raw number between dNCM and vNCM might be similar.…”
Section: Topography Of Ncmsupporting
confidence: 88%
“…Interestingly, the percentage of aromatase neurons detected by both the rabbit (Ikeda et al, 2017) and the sheep antibodies (present study) was slightly higher in the ventral NCM compared to the dorsal NCM (90.5% in vNCM, 86.5% in dNCM) which could partially account for this region-dependence. The dorsal NCM is also known to contain more cells as shown by DAPI staining (Vahaba et al, 2020) and confirmed in the present study that could explain the lower proportion of aromatase positive cells while the raw number between dNCM and vNCM might be similar.…”
Section: Topography Of Ncmsupporting
confidence: 88%
“…In this respect, it is possible that NE infusions into NCM allow for greater tutoring-dependent plasticity within sensorimotor circuitry. Supporting this notion is the finding that neuromodulation within NCM can affect sensory responses within sensorimotor circuitry (86,87). Revealing how NE manipulations in the NCM of juvenile birds affect auditory responses in NCM and HVC or how song learning is affected by NE infusions in NCM coupled with perturbations of HVC activity will be important to differentiate these possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…Songbirds are altricial, and developmental processes in altricial species lag behind those in precocial species (Kubke & Carr, 2000). Still, sparse data in songbirds suggest at least that the auditory forebrain is largely developed before the sensitive period—cell density in NCM of 20 and 30 dph zebra finches is similar to, or even greater than, that in adults (Stripling et al., 2001; Vahaba et al., 2020)—and is mature before the song system. In song motor nuclei, neurogenesis, neural responses, and N‐methyl‐D‐aspartate receptor (NMDAR) expression change significantly during the sensitive period into adulthood (Burek et al, 1991; Nordeen & Nordeen, 2004; Whaling et al., 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular single‐unit recording was performed in vivo in awake‐restrained birds as in previous studies (Miller‐Sims & Bottjer, 2014; Schneider & Woolley, 2013; Vahaba et al., 2020). Subjects were brought into an anechoic chamber and fixed to a stereotaxic apparatus (Herb Adams Engineering) on an air table at a 45° head angle.…”
Section: Methodsmentioning
confidence: 99%